Understanding the relationship between Food Insecurity, Excess Body Weight, and Mental Health among Latinos in California. 2014 - Martinez-Jaikel, Tatiana (2020)
Objectives: 1) To determine the association between food insecurity and excess body weight among Latinos in California, and whether it differs by gender. 2) To examine the role of psychological distress as a mediator in this relationship. Material and Methods: A cross-sectional analysis was conducted in adults participating in the California Health Interview Survey in 2014, who self-reported as Latinos (n=3779). Using logistic regression, we examined the associations of interest while controlling for key covariates. Results: Food insecurity was positive and significantly associated with excess body weight in Latino women, but not men. Psychological distress was positively associated with food insecurity, but not with excess body weight. Conclusions: Psychological distress did not appear to be a mediator in the food insecurity-body weight association in this sample. More studies are needed to fully understand the relationships among mental health, obesity and food insecurity.